SHORT COMMUNICATION: THE EFFECT OF TANNIN SOLUTION IN PERFORMING SUCCESFULL EGG MICROINJECTION ON AFRICAN CATFISH (Clarias gariepinus) - Muhammad Hunaina Fariduddin Ath-thar; Komar Sumantadinata; Alimuddin Alimuddin (Indonesian Aquaculture Journal, 2009)
In order to successfully perform a gene transfer activity using microinjection, an individual egg is needed. The common standard operating procedure to collect the individual egg is by applying chemical solution to remove the sticky layer covering the egg surface. Among several available solutions, tannin is one of alternative substances that can be used in performing egg microinjection on African catfish. In this study, the effect of different dosages of tannin solution to remove the sticky layer of eggs was observed. The study was conducted at the Laboratory of Fish Breeding and Genetics, Bogor Agricultural University. Prior to microinjection, the eggs were treated with different dosages of tannin solution right after fertilization. There were four different levels of dosage used as the treatments i.e.: 0.3, 0.5, 0.7, and 0.9 ppm. After the treatments, each individual egg was injected using DNA pmâactin-hrGFP plasmid with a concentration of 20 μg/mL. The results showed that the dosage of 0.5 ppm of tannin was the most effective treatment compared to the other dosages. This dosage produced 71.4% hatching rate and 57.1% transgenic embryos respectively.